Pengaruh Latihan Half Squat terhadap Kemampuan Tendangan Dollyo Chagi pada Atlet Beladiri Taekwondo - Muhammad Rusli; Marsuna Marsuna; J Jud; S Sariul (Universitas Pendidikan Indonesia, 2023)
Half squat is a strength exercise to improve the ability of the pelvic and thigh muscles by standing straight with the feet shoulder-width apart and the toes facing slightly outward to maintain balance. When the knees bent and the hips lowered, the knees are not going beyond the toes. This study was aimed to determine the effect of half squat training on dollyo chagi kicking skill of Taekwondo athletes. This study used an experimental method using a one group pre-test post-test design. The population of this study were all 20 members of the Kendari City Taekwondo Club. The total sampling technique was used to select the samples. From the results of the data analysis, the pre-test score was 25.95, while the post-test score was 30.35. Based on the results of data analysis, the effect of half squat training on the dollyo chagi kicking skill of Taekwondo athletes was proven significant, as indicated by the t-test value of 0.000 0.05. Based on the results of data analysis, the half squat exercise had a major impact on the ability of Taekwondo athletes to perform dollyo chagi kicks. In addition, the half squat exercise had an effect on increasing the athlete leg muscle power because it was carried out in a programmed exercises repeatedly so that the results of the skill could be maximized as expected.